2009
DOI: 10.1007/s10493-008-9227-x
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear genome of the phytoseiid Metaseiulus occidentalis (Acari: Phytoseiidae) is among the smallest known in arthropods

Abstract: The genome size of the phytoseiid Metaseiulus (=Typhlodromus or Galendromus) occidentalis (Nesbitt) needs to be estimated before the whole nuclear genome can be sequenced. Two different procedures were used to estimate the genome size of M. occidentalis; (1) flow cytometry (Marescalchi et al. in Genome 33:789-793, 1990) and (2) quantitative real-time PCR (qRT-PCR) (Wilhelm et al. in Nucleic Acids Res 31:e56, 2003). Fluorescence intensity of propidium iodide-stained nuclei of M. occidentalis was measured by flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…The products amplified from M. occidentalis were sequenced and were 100% identical to the known sequences. (40) When the genome size of M. occidentalis (88-90 Mb) is compared to other arthropods, it is slightly larger than that of its most important prey, the two-spotted spider mite Tetranychus urticae, which is reported to have a genome size of 75 Mb, (41)(42)(43) and is smaller than the genomes of all other studied arthropods (Fig. 5).…”
Section: Genetic Improvement Through Recombinant Dna Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The products amplified from M. occidentalis were sequenced and were 100% identical to the known sequences. (40) When the genome size of M. occidentalis (88-90 Mb) is compared to other arthropods, it is slightly larger than that of its most important prey, the two-spotted spider mite Tetranychus urticae, which is reported to have a genome size of 75 Mb, (41)(42)(43) and is smaller than the genomes of all other studied arthropods (Fig. 5).…”
Section: Genetic Improvement Through Recombinant Dna Methodsmentioning
confidence: 93%
“…Estimates of the size were obtained using a quantitative real-time PCR (qRT-PCR) protocol and flow cytometry. (39)(40) The flow cytometry results indicated that the genome was significantly smaller (less than 100 Mb) than that of D. melanogaster, which was used as a control, but unambiguous estimates could not be obtained. However, the qRT-PCR protocol with two different genes yielded consistent results.…”
Section: Genetic Improvement Through Recombinant Dna Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apis mellifera, the total complement of the heme biosynthesis pathway could be obtained for the predatory parasitiform mite Metaseiulus occidentalis (hemA: 391339730; hemB: 391332178; hemC: 391347560; hemD: 391331139; hemE: 391332650; hemF: 391341014; hemG: 391332341; hemH: 391348503), that has the smallest chelicerate genome to date (Jeyaprakash and Hoy, 2009a). This indicates that the ability to synthesize heme existed in the ancestral parasitiform lineage.…”
Section: Heme the Centre Of Lifementioning
confidence: 99%
“…The 12S rRNA gene has become a useful molecular marker for species resolution within the phytoseiids because it has a higher sequence divergence (9.5-45 %) than the ITS-2 region (1.2-23 %) between species (Navajas et al 1999;Hoy 2002, 2009b;Okassa et al 2009;Tixier et al 2010). The use of EF-Ia for phylogenetic resolution is still novel in the Phytoseiidae (Jeyaprakash and Hoy 2009a). It is considered to be a single-copy gene within the chelicerates (Brower and DeSalle 1994;Cruickshank 2002;Jeyaprakash and Hoy 2009a) and the faster-evolving intron sequences within this gene could provide species resolution (Cruickshank 2002).…”
Section: Introductionmentioning
confidence: 99%